A função social da empresa em face dos princípios constitucionais da ordem econômica – necessidade de concretização - Oliveira, André Luiz Mattos de (2019)
The company social function is not expressed in the constitutional text, although it is a property social function deployment, and for this reason, it must be considered as one of the constitutional principles of the economic order to be observed by the company in its business activity exercise. From the historical evolution of the company social function, since the Liberal State thought, passing through the Democratic State of Law and the so-called Post-Social or Post Modern State it will be possible to analyze the importance of the applicability and implementation of the company social function institute to support the decrease of social inequalities and improvement of the society life, both by the regulation of the law, and by the certifications obtained by private companies that self-regulate to practice the company social function, as analyzed which certified Natura Cosméticos social practices. For this reason, this research makes a historical analysis of the precedents of the social function of property and of production assets, which gave rise to the protection of business activity and its obligation to society, such as the insertion of the company's social function in Brazilian legislation and its implicit form in the federal constitution of 1988 that through its constitutional principles of the economic order, established for companies that carry out business activity in Brazil, the obligation to pay attention to the norms and practices that go beyond the achievement of profit and seek to protect the environment, employees, and society in general, contributing to the sustainable development of the nation. In addition to these legal forms, there are also business certifications that, in the same way, help in achieving the fulfillment of the social function and welfare of society, through business activity.The hypothesis that it is formulated is that the regulation of the social function in business activity constitutes an efficient tool so that the company social function effectively becomes a reality. Thus, through the hypothetical-deductive method, with the theoretical approach and bibliographical research, at the end it will be exposed possible solutions for the company social function realization.